c
Пошаговое объяснение:
(3/(c+3c^(1/2)) +c/(9-c) ÷(c^(3/2))/(3c^(1/2) -c))⁻²=(3/(c^(1/2) ·(c^(1/2) +3)) +c/(9-c) ·(c^1/2) ·(3-c^(1/2))/c^(3/2))⁻²=(3/(c^(1/2) ·(c^(1/2) +3)) +c/((3-c^1/2)(3+c^(1/2)) ·(3-c^(1/2))/c))⁻²=(3/(c^(1/2) ·(c^(1/2) +3)) +1/(3+c^(1/2))⁻²=((3+c^(1/2))/(c^(1/2) ·(c^(1/2) +3)))⁻²=(1/c^(1/2))⁻²=(c^(1/2))²=c
c
Пошаговое объяснение:
(3/(c+3c^(1/2)) +c/(9-c) ÷(c^(3/2))/(3c^(1/2) -c))⁻²=(3/(c^(1/2) ·(c^(1/2) +3)) +c/(9-c) ·(c^1/2) ·(3-c^(1/2))/c^(3/2))⁻²=(3/(c^(1/2) ·(c^(1/2) +3)) +c/((3-c^1/2)(3+c^(1/2)) ·(3-c^(1/2))/c))⁻²=(3/(c^(1/2) ·(c^(1/2) +3)) +1/(3+c^(1/2))⁻²=((3+c^(1/2))/(c^(1/2) ·(c^(1/2) +3)))⁻²=(1/c^(1/2))⁻²=(c^(1/2))²=c